Franchise business model: Theoretical insights - Rasa Levickaitė; Ramojus Reimeris (Business: Theory and Practice, 2010)
The article is based on literature review, theoretical insights, and deals with the topic of franchise business model. The objective of the paper is to analyse peculiarities of franchise business model and its developing conditions in Lithuania. The aim of the paper is to make an overview on franchise business model and its environment in Lithuanian business context. The overview is based on international and local theoretical insights. In terms of practical meaning, this article should be relevant to entrepreneurs, company owners, and future entrepreneurs planning to set up their own business but lacking the managerial experience, and those who are seeking for effective competitive advantages, opportunities in global environment, and economies affected by recession. The second article of franchise series is dedicated to a related topic dealing with perceived value in franchise business model; the third one is empirical research on Lithuanian travel agencies operating under franchise business model.